2019 IEEE 12th International Conference on Cloud Computing (CLOUD) 2019
DOI: 10.1109/cloud.2019.00028
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Performance Prediction of Spark Cloud Applications

Abstract: Big data applications and analytics are employed in many sectors for a variety of goals: improving customers satisfaction, predicting market behavior or improving processes in public health. These applications consist of complex software stacks that are often run on cloud systems. Predicting execution times is important for estimating the cost of cloud services and for effectively managing the underlying resources at runtime. Machine Learning (ML), providing black box solutions to model the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Maros [22] conducted a cost-benefit analysis of a supervised machine learning model for Spark performance prediction and compared their results with Ernest [23]. In this investigation, they considered the black box and gray box techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Maros [22] conducted a cost-benefit analysis of a supervised machine learning model for Spark performance prediction and compared their results with Ernest [23]. In this investigation, they considered the black box and gray box techniques.…”
Section: Related Workmentioning
confidence: 99%
“…The tools will automate the AI application performance profiling and identify the ML model providing the highest performance prediction accuracy supporting model selection and hyper-parameters tuning. Preliminary results in [4,5,6] have shown that ML models allow to achieve good accuracy (with average percentage error between 5 and 15%) in cloud environments. AI-SPRINT will extend the use of such models to consider AI-based sensors and deep networks partitioned and deployed across computing continua.…”
Section: Performance Modelsmentioning
confidence: 99%
“…Both private and public clouds will be valid targets. Applications will be described as OASIS TOSCA templates 4 describing the topology of their components and their software dependencies. Application templates will support restrictions for the deployment on multiple heterogeneous resources (i.e., including hardware accelerators, e.g., GPGPUs) also at the edge layer, by specific attributes (e.g., the target image, performance constraints or privacy requirements), which will be instantiated and managed by a single interaction with the AI-SPRINT framework.…”
Section: Continuous Deploymentmentioning
confidence: 99%
“…A cost-benefit Spark performance prediction model based on a machine learning algorithm was proposed by Maros [30]. They have proposed both black-box and grey-box models based on four machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%